(untitled) (PROCEEDING OF INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDY, 2025)
International Community Service for Human Resource Development in Kelulut Honey Cultivation Business in Alor Gajah Melaka Malaysia. The purpose of this International Community Service activity is to develop human resources in the Kelulut Honey cultivation business in Alor Gajah Melaka Malaysia. The International Community Service method uses lectures, mentoring, and case studies. The results of the International Community Service are an increase in skills in managing human resources in the Kelulut Honey Cultivation Business in Alor Gajah Melaka Malaysia.